(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The contaminated environmental surfaces are not only potential reservoirs for spread of microbial agents inside hospital but also in community. The development and evolution of antimicrobial resistance in pathogen has been reported to be one of the major issues confronting the global health community. Members of family Enterobacteriacae able to produce extended spectrum of beta lactamase which is responsible to hydrolyze the third generation of cephalosporin group antibiotics resulting treatment failure. The use of beta-lactams has increased considerably since its discovery so also resistant genes leading to Extended-Spectrum Beta-Lactamases (ESBL) mediated by the presence of blaCTX-M, blaTEM, and blaSHV genes present in most Gram-negative bacteria. Out of 300 swab samples collected, 218 (72.7%) bacteria were isolated. 158 (72.5%) was gram positive and 60(27.5%) was gram negative. A total of 96(44.0%) isolates were multidrug resistant. Antibiotics susceptibility test was performed by Kirby Bauer technique according to CLSI guidelines. Organisms that tested positive phenotypically for ESBL were subjected to PCR for molecular analysis. ESBL had a percentage rate of 11.3%. The coexistence of bla CTX-M, bla TEM and bla SHV gene was detected